2023
DOI: 10.1038/s41598-023-38499-7
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled test of emotional attributes of a virtual coach within a virtual reality (VR) mental health treatment

Abstract: We set out to test whether positive non-verbal behaviours of a virtual coach can enhance people's engagement in automated virtual reality therapy. 120 individuals scoring highly for fear of heights participated. In a two-by-two factor, between-groups, randomised design, participants met a virtual coach that varied in warmth of facial expression (with/without) and affirmative nods (with/without). The virtual coach provided a consultation about treating fear of heights. Participants rated the therapeutic allianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Two recent reviews of psychotherapy outcome expectations and credibility beliefs concluded that the CEQ is a psychometrically sound instrument and the most widely used measure of these two constructs (Constantino, Coyne, et al, 2018a; Constantino, Visla, et al, 2018b). Furthermore, it has been validated and is frequently used in an international context to assess credibility and expectancy beliefs for both mental health and physical health interventions (e.g., Haas et al, 2021; Mertens et al, 2016; Silva et al, 2021; Wei et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Two recent reviews of psychotherapy outcome expectations and credibility beliefs concluded that the CEQ is a psychometrically sound instrument and the most widely used measure of these two constructs (Constantino, Coyne, et al, 2018a; Constantino, Visla, et al, 2018b). Furthermore, it has been validated and is frequently used in an international context to assess credibility and expectancy beliefs for both mental health and physical health interventions (e.g., Haas et al, 2021; Mertens et al, 2016; Silva et al, 2021; Wei et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…In face-to-face treatment respect is the foundation of the therapeutic alliance that is so important for successful outcomes. 3 The quality of respect – and warmth too 4 – should be an essential aspect of digital treatments also. Respect in treatment delivery should be obvious to patients, who so often experience the very opposite in their lives.…”
Section: Be Respectfulmentioning
confidence: 99%
“…One may better understand basic processes, such as perception, memory, problem-solving, mental imagery, attention (Gaggioli, 2001), habituation (Li and Lee, 2023), and affect, including empathy (Hapuarachchi et al, 2023), by studying how people interact in virtual reality. One may also design experimental studies in virtual reality that are not possible in real life, such as ones that rigorously test which characteristics of a mental health coach are most effective (Wei et al, 2023).…”
Section: Virtual Realitymentioning
confidence: 99%